2002
DOI: 10.1080/08910600260081748
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bifidobacterium and Lactobacillus spp. in Breast-Fed and Formula-Fed Infants as Assessed by 16S rDNA Sequence Differences

Abstract: A qualitative molecular monitoring approach based on PCR and denaturing gradient gel electrophoresis (DGG E) was used to study the diversity of dominant bacteria, bi dobacteria and lactobacilli in vaginally delivered full-term infants. Seven breast-fed and six formula-fed infants participated in the study. 16S rDNA targeted primers were used for the speci c PCR ampli cation of fragment s from bacteria, bi dobacteria and lactobacilli from faeca l samples that were collected before and after weaning at the age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 31 publications
4
39
0
4
Order By: Relevance
“…We also observed that during weaning, breastfeeding induced a slower increase of C. leptum and a faster reduction of C. difficile and C. perfringens species compared with formula or mixed feeding. Satokari et al (2002) reported similar changes in the microbiota during weaning between breastfed and formula-fed infants. In a group of children at 6 months, where half had started to have the breast milk supplemented with solid food, George et al (1996) observed that the number of enterococci and Bacteroides increased, whereas enterobacteria and bifidobacteria remained constant.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…We also observed that during weaning, breastfeeding induced a slower increase of C. leptum and a faster reduction of C. difficile and C. perfringens species compared with formula or mixed feeding. Satokari et al (2002) reported similar changes in the microbiota during weaning between breastfed and formula-fed infants. In a group of children at 6 months, where half had started to have the breast milk supplemented with solid food, George et al (1996) observed that the number of enterococci and Bacteroides increased, whereas enterobacteria and bifidobacteria remained constant.…”
Section: Discussionmentioning
confidence: 66%
“…This is reflected in the microbiota composition and profiles of short chain fatty acids (Midtvedt & Midtvedt, 1992). There are, however, very little data on changes in the composition of the intestinal microbiota during early weaning (Satokari et al, 2002;Wang et al, 2004;Ahrné et al, 2005) and how the influence of pre-weaning feeding methods and perinatal events impact on the microbiota after the introduction of complementary foods.…”
Section: Introductionmentioning
confidence: 99%
“…While there were marked differences between the EBF and EBF C S groups, the separation between clusters of non-EBF and non-EBF C S groups was more distinct. The lack of any significant microbiota changes accompanying the introduction of complementary foods reported in BF infants by some groups 22,43 further supports the impact of HM withdrawal. Others have found that infants still receiving HM at 9 mos harbored lower levels of butyrateproducing bacteria, C. leptum, C. coccoides, and Roseburia, as well as Bacteroidetes 45 which have been previously noted to increase when infants begin to consume solid foods.…”
Section: Weaning Complementary Feeding and Introduction Of Solidsmentioning
confidence: 57%
“…58 Infants harboring similar relative abundances of Bifidobacterium still exhibit some variance in diversity, 34,39,42 and stability 51 of populations at the species level. For example, B. longum and B. breve are the dominant species in BF infants, 27,[41][42][43] whereas FF infants also harbor adultassociated bifidobacterial species, such as B. adolescentis. 24,39,42 While many studies have focused on bifidobacterial colonization, breastfeeding supports other differences in microbiota composition.…”
Section: (Finland)mentioning
confidence: 99%
See 1 more Smart Citation